2012
DOI: 10.1021/ol203329u
|View full text |Cite
|
Sign up to set email alerts
|

Direct Glycosylation of Unprotected and Unactivated Carbohydrates under Mild Conditions

Abstract: Ligand exchange acetalization of acetals in the presence of catalytic amounts of mandelic acid and titanium tert-butoxide is reported. This transformation is successfully extended to glycosylation of unprotected and unactivated pentoses. Even unreactive pentoses such as D-arabinose or D-lyxose can be transformed by this new methodology into corresponding isopropyl glycosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…In an attempt to find a suitable robust donor capable of being activated in its unprotected state, Roy and Mukhopadhyay performed Fischer‐type glycosylation to establish the use of H 2 SO 4 –silica to couple unprotected free sugars with different alcohols . Interestingly, Pfaffe and Mahrwald showed that, when variously functionalized alcohols were reacted with free d ‐ribose 175 catalyzed by 10 mol % of titanium‐(IV) tert ‐butoxide and 50 mol % d ‐mandelic acid at room temperature, only coupled ribose furanosides (Scheme ) were obtained …”
Section: Glycosylationsmentioning
confidence: 99%
“…In an attempt to find a suitable robust donor capable of being activated in its unprotected state, Roy and Mukhopadhyay performed Fischer‐type glycosylation to establish the use of H 2 SO 4 –silica to couple unprotected free sugars with different alcohols . Interestingly, Pfaffe and Mahrwald showed that, when variously functionalized alcohols were reacted with free d ‐ribose 175 catalyzed by 10 mol % of titanium‐(IV) tert ‐butoxide and 50 mol % d ‐mandelic acid at room temperature, only coupled ribose furanosides (Scheme ) were obtained …”
Section: Glycosylationsmentioning
confidence: 99%
“…252 Bypassing many of the previously examined challenges in carbohydrate chemistry, including multistep protection sequences and selective activation requirements, this glycosylation protocol presents a unique approach to the activation of the anomeric center using titanium(IV) alkoxides and α-hydroxy acids (Scheme 31). …”
Section: 1- Hydroxy Sugar Donorsmentioning
confidence: 99%
“…The most obvious improvement is to await a method that provides furanosyl glycosides in preference to pyranosides when furanose donors are employed, thus obviating the need for any protecting groups. We also credit the outstanding efforts of the Mahrwald group for being able to develop a catalytic methodology for the synthesis of aliphatic or benzylic glycosides under neutral conditions [117118]. We are looking forward to seeing if any expansion of the substrate scope to more complex acceptors is possible and forthcoming.…”
Section: Resultsmentioning
confidence: 98%
“…13 [117]. The yields ranged from very moderate to nearly quantitative and the reaction was reasonably stereoselective for the 1,2- trans product.…”
Section: Reviewmentioning
confidence: 99%